The urgency of protecting traditional knowledge of medicines as communal intellectual property of the Aceh community - Yulia Yulia (Geuthèë Institute, Aceh, 2023)
Traditional knowledge is part of the communal intellectuals of the Acehnese people who need recognition and protection. Knowledge of traditional medicine is part of the knowledge of traditional Acehnese society which is expressly recognized in the 1945 Constitution that recognition of community rights, including knowledge of traditional medicine. There are many cases of patenting of traditional medicinal knowledge by companies outside the country, such as herbal medicine for the Javanese community by the Shiseido company in Japan. This article aims to examine the urgency of protecting traditional knowledge as the communal intellectual property of the people of Aceh. This study uses normative legal research methods using data from literature studies and laws and regulations. This study finds that there is an urgency to protect traditional medicines against various violations of intellectual property rights which are very detrimental to the community holding communal intellectual property rights. In order to protect the law, the government has issued a government regulation regarding the collection of data on communal intellectual property. Apart from that, the laws and regulations on intellectual property rights also contain articles that support the protection of communal intellectual property such as the Copyright Law and the Patent Law. Then also, the use of intellectual property increases economic value and can eliminate the identity of the intellectual property of the people of a region. Thus, further strengthening measures to protect the communal intellectual property of the people in Aceh.